2017
DOI: 10.1111/bju.13846
|View full text |Cite
|
Sign up to set email alerts
|

Unprofessional content on Facebook accounts of US urology residency graduates

Abstract: ObjectiveTo characterize unprofessional content on public Facebook accounts of contemporary US urology residency graduates. MethodsFacebook was queried with the names of all urologists who graduated from US urology residency programmes in 2015 to identify publicly accessible profiles. Profiles were assessed for unprofessional or potentially objectionable content using a prospectively designed rubric, based on professionalism guidelines by the American Urological Association, the American Medical Association, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 19 publications
(29 reference statements)
2
61
0
5
Order By: Relevance
“…While graduating residents' and consultants' 21 limited awareness of guidelines and legislations are concerning, as posting unprofessional content online has resulted in disciplinary action, [23][24][25] these finding highlight an opportunity to help urologists. Post-graduate medical educators can encourage residents to become more aware of SoMe policies, as there are roles for practicing safe and responsible SoMe use under several CanMEDS (Canada's framework for physician training) competencies.…”
Section: Awareness Of Guidelines and Legislationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While graduating residents' and consultants' 21 limited awareness of guidelines and legislations are concerning, as posting unprofessional content online has resulted in disciplinary action, [23][24][25] these finding highlight an opportunity to help urologists. Post-graduate medical educators can encourage residents to become more aware of SoMe policies, as there are roles for practicing safe and responsible SoMe use under several CanMEDS (Canada's framework for physician training) competencies.…”
Section: Awareness Of Guidelines and Legislationsmentioning
confidence: 99%
“…22 These concerns are valid, as some physicians and medical trainees have experienced disciplinary action for posting inappropriate content. [23][24][25] Several medical organizations have developed professional SoMe use guidelines in response to these concerns. [26][27][28][29][30][31][32] Specific to urologists, BJU International (BJUI) and the European Association of Urology (EAU) have published guidelines for effective and responsible SoMe use.…”
Section: Introductionmentioning
confidence: 99%
“…A review of social media accounts from newly graduated urology residents found 40% had authored unprofessional or potentially objectionable content. 17 Given the pervasive use of social media among students, professional standards for social media interaction should be incorporated into the medical education curriculum to help physicians establish an appropriate and impactful social media presence. …”
Section: Potential Pitfallsmentioning
confidence: 99%
“…The recent paper by Koo et al on ‘unprofessional’ online content amongst American urology residency graduates has received attention in the lay press and social media outlets. The paper has an Altmetric Attention score of 341 – good for the fifth most online‐cited paper the BJUI has ever published.…”
mentioning
confidence: 99%
“…This study is, to borrow a new hackneyed American aphorism, fake news. BJUI promotes intellectual discourse through responsible use of social media, yet this study muzzles free speech by stigmatising expression.…”
mentioning
confidence: 99%